2017
DOI: 10.1002/jrs.5310
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in linear and non‐linear Raman spectroscopy. Part XI

Abstract: This review, published annually, provides an overview of advances in the field of Raman spectroscopy as found in papers published in the preceding calendar year in the Journal of Raman Spectroscopy (JRS), as well as in trends over the past decade across journals that have published papers important to the field of Raman spectroscopy. This information is obtained from statistical data on article counts obtained from Clarivate Analytics' Web of Science Core Collection by year and by subfield of Raman spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 203 publications
0
15
0
Order By: Relevance
“…Korsakov and Marshall presented a conference and special issue overview for the JRS Special Issue devoted to GeoRaman 2016 held in Novosibirsk, Russia, attended by 102 conferees from 16 countries . Finally, Nafie published the 2017 version of the present review, which provides an overview of advances in the field of Raman spectroscopy as found in papers published in 2016 in the JRS , as well as in trends over the past decade across journals that have published papers important to the field of Raman spectroscopy …”
Section: Special Issues and Reviewsmentioning
confidence: 99%
See 3 more Smart Citations
“…Korsakov and Marshall presented a conference and special issue overview for the JRS Special Issue devoted to GeoRaman 2016 held in Novosibirsk, Russia, attended by 102 conferees from 16 countries . Finally, Nafie published the 2017 version of the present review, which provides an overview of advances in the field of Raman spectroscopy as found in papers published in 2016 in the JRS , as well as in trends over the past decade across journals that have published papers important to the field of Raman spectroscopy …”
Section: Special Issues and Reviewsmentioning
confidence: 99%
“…[250] Finally, Nafie published the 2017 version of the present review, which provides an overview of advances in the field of Raman spectroscopy as found in papers published in 2016 in the JRS, as well as in trends over the past decade across journals that have published papers important to the field of Raman spectroscopy. [11]…”
Section: Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…A perspective review of the field of Raman spectroscopy is published annually in the Journal of Raman Spectroscopy (JRS), first initiated in 2007 and continued through 2018 in which highlights of current trends in Raman spectroscopy are presented. The 2019 review incudes coverage of papers published in the JRS during calendar year 2018 as well as a survey of Raman topics included in conference programs this year at (a) the Tenth International Conference on Advanced Vibrational Spectroscopy (ICAVS 10) in Aukland, New Zealand in July; (b) SCIX 2019 organized by the Federation of Analytical Chemistry and Spectroscopy Societies (FACSS) in Palm Springs, California USA in October; (c) the European Conference on Nonlinear Optical Spectroscopy (ECONOS 2019) in Rouen, France in April; and (d) the Tenth International Congress on the Application of Raman Spectroscopy in Art and Archaeology (RAA 2019) in Potsdam, Germany in September.…”
Section: Introductionmentioning
confidence: 99%